Menjaga Efektifitas Supervisi Pendidikan Paska Pandemi - Riani, Lilia Pasca; Sari, Ika Novita; Khasanah, Sarifatun; Putri, Anisa Eka (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2022)
The purpose of this study is to describe the real conditions related to the supervision carried out by school principals during the pandemic. Even though learning is done at home, the implementation must be following applicable regulations and teachers must remain disciplined in administration. This research is a field study with a qualitative approach. Data collection techniques used interviews and observations with principals, teachers, parents, and students at elementary schools in the Sleman Regency, DIY, while information collection used snowball sampling. Data analysis techniques used 1) data reduction, 2) data presentation and 3) data verification. The results of the study show 11 characteristics of school principal supervision to maintain the effectiveness of educational supervision during the pandemic.